Arbitrary pole placement by state feedback with minimum gain - Schmid, R.; Ntogramatzidis, Lorenzo; Nguyen, T.; Pandey, A. (Institute of Electrical and Electronics Engineers ( IEEE ), 2013)
We consider the classic problem of pole placement by state feedback. We offer an eigenstructure assignment algorithm to obtain a novel parametric form for the pole-placing gain matrix that can deliver any set of desired closed-loop eigenvalues, with any desired multiplicities. This parametric formula is then exploited to introduce an unconstrained nonlinear optimisation algorithm to obtain a gain matrix that delivers the desired pole placement with minimum gain.